The harvest of freshwater crayfish, Astacus leptodactylus (Eschscholtz, 1823) in Turkey - Harlioglu, MM; Harlioglu, AG (Springer, 2004)
Astacus leptodactylus is naturally and widely distributed in lakes, ponds and rivers throughout of Turkey. It has also been stocked in many freshwater systems in Turkey to establish new populations and to restore crayfish stocks devastated by the plague (Aphanomyces astaci) and some other reasons (i.e., farming and culinary purposes). Human consumption of A. leptodactylus has always been very low in Turkey; therefore, it was exported mainly to Europe until 1986. A plague was observed in 1985 in Egirdir, Apolyont, Sapanca and Manyas lakes which included the main harvest areas, and the fishery was lost within 2 years. Consequently, crayfish harvest was banned in all populations to control the plague. Because of the plague, over-fishing and pollution, the harvest of A. leptodactylus in Turkey declined from approximately 5000 (1984) to 200 (1991) tons annually. In 2000s, there has been a gradual increase in the rate of harvest of A. leptodactylus in Turkey, reaching approximately 1600-1900 tons annually, but the plague is still observed in this species at certain localities. The present study reveals that A. leptodactylus in Turkey needs professional support for recovery, because the present harvest of A. leptodactylus is still nearly 20% of the crayfish catch in 1980s.
Keywords: Astacus leptodactylus; crayfish; harvest; management; plague; production; Turkey